Magnesium citrate malate as a source of magnesium added for nutritional purposes to food supplements. (6th December 2018) - ,; Turck, Dominique; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; et al.
Abstract: The present scientific opinion deals with the assessment of the bioavailability of magnesium, from the proposed nutrient source, magnesium citrate malate (MgCM), when added for nutritional purposes to food supplements. MgCM is a mixed salt consisting of magnesium cations and citrate and malate anions, and with a magnesium content of 12–15%. MgCM is proposed to be used in food supplements that are intended to provide up to 300–540 mg/day magnesium. The data provided demonstrate that the production process results in batches of MgCM that comply with the product specifications and that the product is stable throughout its proposed shelf life. The human studies provided demonstrate that magnesium from MgCM is bioavailable. However, the extent of its bioavailability per se or compared to other magnesium sources cannot be established due to the lack of an appropriate magnesium source as a comparator in the studies provided or relevant kinetic data for magnesium. One publication provided in the dossier reported that supplementation with MgCM decreases calcium absorption, but this finding was not supported by publications on different magnesium salts and therefore the Panel could not draw conclusions from this finding. The Panel concludes that MgCM is a source from which magnesium is bioavailable, but the extent of its bioavailability cannot be established. The Panel notes that at the proposed maximum use levels of MgCM, the existing tolerable upper intake level for magnesium in nutritional supplements, water, or added to food and beverages (250 mg/day) is exceeded.